A minimum of 1‐year follow‐up for MiniArc single incision slings compared to Monarc transobturator slings: An analysis to evaluate durability of continence and medium‐term outcomes. Issue 3 (5th May 2016) - Tutolo, Manuela; De Ridder, Dirk J.M.K.; Montorsi, Francesco; Castagna, Giulia; Deprest, Jan; Schellart, Renè P.; Ammirati, Enrico; Van Der Aa, Frank
Abstract : Aims: To compare efficacy and safety of two commercially available single incision slings (SIS) and trans‐obturator vaginal tapes (TOT), namely MiniArc™ and Monarc™ slings, and report the results at 5‐year follow‐up. Methods: A retrospective‐observational study of prospectively collected data was conducted on 381 women with primary stress urinary incontinence (SUI) in a single tertiary referral center. Patients treated with MiniArc™ and Monarc™ were compared. Data regarding intraoperative and post‐operative outcomes were collected and compared. Kaplan–Meier analyses assessed continence rate (CR), objective cure (OC) rate, de novo overactive bladder symptoms (OAB), surgical failure (SF), and erosion free rates at 1‐, 3‐, and 5‐year follow‐up. The log‐rank test was used to compare efficacy and complication between patients stratified according to the type of surgery. Results: Median follow‐up was 60 months. Of 381 patients, 215 (56%) were treated with Monarc™ slings and 166 (44%) with MiniArc™. The two groups were homogeneous in terms of pre‐operative characteristics. At 5‐year follow‐up, no difference was found in CR between Monarc™ and Miniarc™ patients (87% vs. 89%; P = 0.41). Monarc™ showed better OAB free rates (97% vs. 92%; P = 0.012). No significant differences have been found in terms of SF, erosion, and OC rates. These results are limited by their retrospective nature. Conclusions: We demonstrated that the short‐term results of MiniArc™, are maintained over time, defining the comparability of the two slings at 5 years in terms of subjective and objective outcomes and complications. Neurourol. Urodynam. 36:803–807, 2017 . © 2016 Wiley Periodicals, Inc.